MANAJEMEN PENGEMBANGAN KURIKULUM BERBASIS INTEGRASI KEILMUAN - Abdi Abdi (Kelola: Journal of Islamic Education Management, 2023)
This study aims to determine the form/model, development management, internal and external factors and alternative strategies in the Scientific Integration-Based Curriculum implemented in the Muhammadiyah Boarding School of Palopo. This research use desciptive qualitative approach. The research was conducted at MBS Palopo. The research subjects were primary subjects consisting of the Director of SBM, the curriculum development team and teachers as well as secondary subjects, namely the results of documentation. Techniques and data collection instruments used were observation, interviews and documentation. Test the validity of the data through the triangulation process. The results of this study indicate that the curriculum structure with an integrated curriculum model aims to facilitate students with general knowledge and religious knowledge. In the management of scientific integration-based curriculum development at the Muhammadiyah Boarding School Palopo, there are several stages of the process, namely; curriculum planning, curriculum organizing, curriculum monitoring and curriculum improvement. Internal and external factors that contribute to the management of scientific integration-based curriculum development at the Muhammadiyah Boarding School Palopo. The results of the analysis of internal and external factors show that the strengths of MBS Palopo are able to overcome its weaknesses and be responsive in dealing with threats in curriculum development. An alternative strategy in developing a scientific integration-based curriculum at the Muhammadiyah Boarding School. The first strategy is to organize training such as workshops on a national or international scale. The second strategy is to facilitate teachers in every SBM activity and facilitate teachers in strengthening the literacy movement. The third strategy is opening up space for private institutions in developing the teaching profession.